2018
DOI: 10.1002/cbm.2083
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and alexithymia: Are there differences between traditional, cyber, combined bullies, and nonbullies in reading their own emotions?

Abstract: Alexithymia is thus likely to be an important factor to consider in prevention and treatment of bullying. We recommend that prevention programmes include elements to help identify and describe one's own emotions, providing additional support, and "training" if alexithymia is identified. When young people use cyber techniques and traditional bullying methods, it seems likely that they will have greatest need in this respect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
1
9
0
2
Order By: Relevance
“…The third hypothesis had support, where alexithymia was positively correlated with cyberbullying perpetration. This finding is in line with previous work [ 20 , 26 ] and theoretically with the General Aggression Model [ 21 ] that postulates that personality traits contribute to aggressive behaviors in humans. Among some adolescents, alexithymia facilitates interpersonal problems, uncontrolled emotional responses, expressions of anger, and aggressive behavior, which has been broadly shown in other studies on the associations between alexithymia and aggressive behavior [ 22 , 23 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The third hypothesis had support, where alexithymia was positively correlated with cyberbullying perpetration. This finding is in line with previous work [ 20 , 26 ] and theoretically with the General Aggression Model [ 21 ] that postulates that personality traits contribute to aggressive behaviors in humans. Among some adolescents, alexithymia facilitates interpersonal problems, uncontrolled emotional responses, expressions of anger, and aggressive behavior, which has been broadly shown in other studies on the associations between alexithymia and aggressive behavior [ 22 , 23 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, core characteristics of alexithymia include a lack of social attachment and social skills, which might further contribute to the association between alexithymia and cyberbullying perpetration [ 13 , 17 ]. Indeed, initial research has shown that both traditional and cyber bullies show higher levels of alexithymia [ 20 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past research showed that age, sex, and cyberbullying perpetration is correlated with cyberbullying victimization and alexithymia (Tokunaga, 2010;Brody and Vangelisti, 2017;Wachs et al, 2017;Wachs and Wright, 2018).…”
Section: Control Variablesmentioning
confidence: 99%
“…The term alexithymia is used to describe disturbance in affect regulation characterized by a difficulty in identifying and verbalizing differentiated feelings, a way of thinking which focuses primarily on the actual aspects of external circumstances rather than subjective experiences and by a limited fantasy life (Kooiman et al, 2004). It has been found that alexithymia plays an important role in the links between inadequate parenting and adjustment problems (Taylor & Bagby, 2012;Van der Velde et al, 2013), such as the expression of violent behavior (Wachs & Wright, 2018) and, in particular, dating violence (Moral de la Rubia & Ramos-Basurto, 2015), cyberbullying and cybervictimization (Aricak & Ozbay, 2016), and CPV (Lozano- Martínez, Estévez, & Carballo-Crespo, 2013). However, there are few studies in which implications of parenting styles in alexithymia, especially in community samples, are examined.…”
mentioning
confidence: 99%